ANALISIS YURIDIS PERATURAN KEPALA BADAN PERTANAHAN NOMOR 3 TAHUN 1997 DITINJAU DARI UNDANG-UNDANG NOMOR 4 TAHUN 1996 MENGENAI ROYA PARTIAL (STUDI KASUS KANTOR PERTANAHAN KOTA MEDAN) - SATRIO ADI NUGROHO (PREMISE LAW JURNAL, 2016)
The obstacle faced by the Land Office in Medan in implementing partial cancellation of hypothecation after the issuance of the Decree of the Agrarian Minister of State/the Head of the National Land Agency No. 3/1997 is that collateral objects as the hypothecation in a credit contract by debtor as the giver of hypothecation is the land and building rights as one ownership so that partial cancellation cannot be done. Some efforts made by the Land Office, Medan, with the different opinion on the implementation of partial cancellation according to the Decree of the Agrarian Minister of State/the Head of the National Land Agency No. 3/1997 is by doing some approaches and appeals to Notaries/PPAT (official empowered to draw up land deeds) to make declaration on hypothecation holder in authentic deeds in order to release a part of the hypothecation by attaching clearly which part of it which is released by the Hypothecation. Keywords: Partial Cancellation, Hypothecation, the Land Office of Medan